Effect of income diversification on the livelihood of rural farming households in Kwara State, Nigeria - Funmilayo Omotesho, Kemi; Felix Akinrinde, Adeniyi; Ogunlade, Israel; Kekinde Egbugo, Juliana (Kasetsart Journal of Social Sciences, 2020)
Challenges such as those poised by climate change and farmers-herdsmen conflicts have increased income diversification among farmers in Nigeria. While rural income diversification has been applauded as insurance against the risks inherent in farming, its potentials to compete for the resources and attention of farmers may have negative consequences for agricultural production food security, and the livelihood of rural households. Specifically, the study described the socio-economic characteristics of rural households in the study area, examined the number of income sources of rural households, determined the contributions of different income sources to the overall household income, and assessed the livelihood status of rural households. A three-stage random sampling technique produced a sample size of 160. Data was obtained through an interview schedule. Descriptive statistics and Pearson’s Product Moment Correlation were used for data analyses. Findings revealed that rural household heads were predominantly male (85%), with a mean age of 51.6 years. The mean annual income and farm size were 2,002.57 and 3.3 acres respectively. The average number of income sources was 3.3 and farming contributed the most (40.4%) to household income. The Livelihood status of the respondents was low (mean = 1.77). At p < .01 households’ number of income sources was inversely related to their livelihood status. The study concluded that the more diverse farmers’ income, the lower their livelihood status. It is recommended that the number of their economic activities are kept at such that can be effectively managed for positive contributions to the livelihood of farming households.